2020
DOI: 10.1016/j.ajodo.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress in orthodontic patients during the coronavirus disease 2019 pandemic

Abstract: Introduction The ongoing coronavirus disease 2019 (COVID-19) outbreak impacts the mental health of patients, health workers, and the public. The level of impact on the mental health of orthodontic patients in treatment is unknown. The objective of the study was to evaluate the mental health of orthodontic patients in China during the early stage of the pandemic. Methods An online survey was conducted on a convenience sample of anonymous participants. The questionnaire, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 29 publications
4
73
3
5
Order By: Relevance
“…This re lects the level of awareness and anxiety they have towards this pandemic and it is the orthodontist responsibility to make them reassured that proper infection control, use of personal protection equipment will be used to prevent the spread of the disease. (Xiong et al, 2020) found that over one-third of orthodontic patients experienced psychological distress during COVID-19 pandemic and some of the main factors affecting the level of anxiety was the type of orthodontic appliance, time since last review appointment, contact with their specialist during dental emergency.…”
Section: Discussionmentioning
confidence: 99%
“…This re lects the level of awareness and anxiety they have towards this pandemic and it is the orthodontist responsibility to make them reassured that proper infection control, use of personal protection equipment will be used to prevent the spread of the disease. (Xiong et al, 2020) found that over one-third of orthodontic patients experienced psychological distress during COVID-19 pandemic and some of the main factors affecting the level of anxiety was the type of orthodontic appliance, time since last review appointment, contact with their specialist during dental emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was the recommendation to use virtual assistance (Eliades & Koletsi, 2020;Maspero et al, 2020;Saccomanno et al, 2020) and assessments regarding the impact of the pandemic on orthodontic consultations and on the anxiety generated in patients and professionals (Martina et al, 2020;Peloso et al, 2020;Cotrin et al, 2020;Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Assessments regarding the impact of the pandemic on the orthodontic consultations and on the anxiety generated in patients and professionals were carried out through questionnaires. It was observed that the level of anxiety was more related to women than to men and that the greatest concern was associated with delayed treatment (Martina et al, 2020;Peloso et al, 2020;Cotrin et al, 2020;Xiong et al, 2020). Fixed lingual appliances and invisible aligners were less associated with high levels of anxiety about the duration of treatment compared to conventional fixed appliances (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations